Features of the Economic and Social Life in Palestine as Illustrated by the Book of Behavior of Al-Maqrizi in 845 Hijri (Global Journal of Human-Social Science, 2019)
Palestine is considered one of the most important civilization in history a lot of chronicler give attention to it in the Islamic era its geographical position is one of the main reason for that along with its importance to all the religious two of the most important battles happened on this land which are Hattin and Ain Goliath which made the chronicler to give it more interest and describe its people and the land in a way that give it more attention they never talk about Egypt without mentioning Palestine which show the deep connection and the importance between both countries
Keywords: Al Maqrizi- the behavior- industry- palestine- trading